A Relational Approach to Understanding Welfare Recipients' Transitions from Long-Term Unemployment to Employment and the Role of Case Work - Andreas Hirseland; Lukas Kerschbaumer (Social Work and Society, 2023)
In Germany, the great majority of long-term unemployed face difficulties in (re-)entering the labour market due to a variety of barriers, including insufficient educational and/or vocational qualifications, poor health, migration background, language deficits, being over 50 years old, and family care responsibilities. However, the work-first approach of German employment services has difficulties in overcoming the multitude of these barriers. In contrast to many quantitative analyses on the topic, our qualitative study adopts a relational-theoretical approach. This approach combines synchronicity and diachronicity perspectives to analyse the conditions that enable transitions into sustainable and sufficient employment, despite the aforementioned adversities. Based on 33 cases of long-term unemployed we used biographical interviews and a modified qualitative network analysis to identify factors that hinder or facilitate such unlikely transitions into the primary labour market. Our findings suggest that a "life-first approach" referring to the lifeworld of individuals can increase the likelihood of these transitions and retention in employment. Therefore, our findings imply that casework focused on lifeworld and biography holds the greatest potential for providing institutional support to these individuals.